Involvement of brain-derived neurotrophic factor and neurogenesis in oestradiol neuroprotection of the hippocampus of hypertensive rats - Pietranera, Luciana (2010)
The hippocampus of spontaneously hypertensive rats (SHR) and deoxycorticosterone (DOCA)-salt hypertensive rats shows decreased cell proliferation and astrogliosis as well as a reduced number of hilar cells. These defects are corrected after administration of 17β-oestradiol (E(2) ) for weeks. The present work investigated whether E(2) treatment of SHR and of hypertensive DOCA-salt male rats modulated the expression of brain-derived neurotrophic factor (BDNF), a neurotrophin involved in hippocampal neurogenesis. The neurogenic response to E(2) was simultaneously determined by counting the number of doublecortin-immunopositive immature neurones in the subgranular zone of the dentate gyrus. Both hypertensive models showed decreased expression of BDNF mRNA in the granular zone of the dentate gyrus, without changes in CA1 or CA3 pyramidal cell layers, decreased BDNF protein levels in whole hippocampal tissue, low density of doublecortin (DCX)-positive immature neurones in the subgranule zone and decreased length of DCX+ neurites in the dentate gyrus. After s.c. implantation of a single E(2) pellet for 2 weeks, BDNF mRNA in the dentate gyrus, BDNF protein in whole hippocampus, DCX immunopositive cells and the length of DCX+ neurites were significantly raised in both SHR and DOCA-salt-treated rats. These results indicate that: (i) low BDNF expression and deficient neurogenesis distinguished the hippocampus of SHR and DOCA-salt hypertensive rats and (ii) E(2) was able to normalise these biologically important functions in the hippocampus of hypertensive animals.